2021
DOI: 10.4274/tjo.galenos.2020.88137
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Findings of Pediatric Dry Eye Related to Graft-Versus-Host Disease

Abstract: Objectives: To evaluate the frequency and findings of dry eye associated with ocular graft-versus-host disease (GVHD) in pediatric hematopoietic stem cell transplantation (HSCT) patients. Materials and Methods: Retrospectively the records of pediatric patients with ocular GVHD were evaluated and ophthalmologic examination findings as well as Schirmer test results, tear film break-up time, and corneal staining grades were recorded. In severe dry eye patients topical cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
2
1
Order By: Relevance
“…Several studies have reported a lower prevalence of systemic GvHD in pediatric cases when compared to adults. [ 10 , 21 , 22 ] This contrasts with our study where the proportions were similar in both the groups ( P = 0.97). Furthermore, the prevalence of dry eye has also been noted to be lower in pediatric patients, whereas in the present study, a similar severity and rate of progression were observed in both groups.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported a lower prevalence of systemic GvHD in pediatric cases when compared to adults. [ 10 , 21 , 22 ] This contrasts with our study where the proportions were similar in both the groups ( P = 0.97). Furthermore, the prevalence of dry eye has also been noted to be lower in pediatric patients, whereas in the present study, a similar severity and rate of progression were observed in both groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, the prevalence of dry eye has also been noted to be lower in pediatric patients, whereas in the present study, a similar severity and rate of progression were observed in both groups. [ 10 , 23 , 24 ] These differences could be attributed to the variable racial and ethnic backgrounds of the samples in the existing literature. Hébert et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation